21st-Century Skills Implementation in Teaching English at Primary School - Kristyaningdih, Ni Komang; Padmadewi, Ni Nyoman; Sulistia Dewi, Ni Luh Putu Eka; Artini, Luh Putu (International Journal of Language and Literature, 2022)
This study aimed to analyze the implementation of 21st-century skills in teaching English at primary schools, such as in Public and Private Schools. This study used mixed method research design, especially the exploratory mixed methods designs. This study was taken place in primary schools in Karangasem Regency. There were 3 schools as the representative of Public Primary schools in Karangasem Regency, such as SDN 1 Kubu, SDN 4 Dukuh and SDN 4 Tulamben. Besides, the representative of Private Primary school was SD Insan Mandiri. Eight teachers were selected using a convenient sampling method. The instruments used in this study were questionnaires, observation, and interview guides. It was found the English teachers in the primary schools in Karangasem Regency were not ready in implementing 21st-century skills in the schools since there were several skills have not been implemented in the lesson plan and assessment. Meanwhile, all skills have been implemented in the teaching and learning process. It can be concluded that 21st-century skills in the primary schools were not implemented well.